ANALYTICAL AND SIMULATED STUDY OF A BIPOLAR TRANSISTOR'S INPUT CHARACTERISTICS USING NI MULTISIM 14.2 PROGRAM - Abdullah Z. Nuri (Journal for Technology and Science, 2026)
Objective: This research presents a comprehensive study of the input characteristics of an NPN transistor in a common-emitter configuration using NI Multisim 14.2 at a constant output voltage across the transistor (VCE = 2 V). Method: The research methodology focuses on the increase in base current (Ig)   as a result of the voltage increase (VBE). The switching voltage, i.e., the critical operating point, is determined using the dynamic resistance equation. Results: The results obtained from NI Multisim 14.2 and the mathematical equations for a silicon diode that accepts or consumes a lower voltage (approximately 0.8 V) are crucial. Novelty: The most important conclusion of this research is that these calculations, relating to base current, emitter-base voltage, and a low dynamic resistance (7.58 Ω), form the basis for designing electronic circuits and the switching and amplification processes they undergo.